2020
DOI: 10.1016/j.euros.2020.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Scheduling Appointments for Postvasectomy Semen Analysis Has No Impact on Compliance

Abstract: Background A postvasectomy semen analysis (PVSA) is recommended 8–16 wk after vasectomy to ensure azoospermia. Patient compliance with submitting a semen sample for PVSA has historically been low. To increase patient compliance, a policy change was made to schedule patients for PVSA appointments instead of a previous “drop-in” option. Objective To compare patient compliance for PVSA when scheduling appointments as opposed to a “drop-in” appointment 8–16 wk after the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…Our results join a body of work where numerous approaches have been studied in attempting to increase PVSA completion rates, though none have been proven to show a consistent advantage ( 6 , 8 , 10 , 12 ). Data is equivocal regarding the value of a separate appointment for PVSA completion.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Our results join a body of work where numerous approaches have been studied in attempting to increase PVSA completion rates, though none have been proven to show a consistent advantage ( 6 , 8 , 10 , 12 ). Data is equivocal regarding the value of a separate appointment for PVSA completion.…”
Section: Discussionsupporting
confidence: 68%
“…Data is equivocal regarding the value of a separate appointment for PVSA completion. In a retrospective analysis of 387 vasectomy patients, Jacobsen et al compared PVSA compliance rates with drop-in style appointments 8–16 weeks after vasectomy versus mandated, scheduled PVSA appointments at time of vasectomy and found no significant differences ( 12 ). However, a study by Dhar et al , 2007 investigating a similar comparison found that among 228 men, 65% returned for PVSA without an appointment while those with pre-scheduled PVSA appointment returned 84% of the time ( 13 ).…”
Section: Discussionmentioning
confidence: 99%